Factors affecting Nepalese rural dwellers' choice of first-contact health facility: a cross-sectional survey - Hocheol Lee; Hyeyeon Jo; Biraj Man Karmacharya; Bimala Sharma; Pramita Shrestha; Prajwal Satyal; Eun Woo Nam (Inishmore Laser Scientific Publishing Ltd, 2023)
# Background Despite significant progress in Nepal's health indicators over the past three decades, regional disparities in public health centre (PHC) provision and accessibility remain severe. It has been reported that rural dwellers prefer and place more trust in outreach centres (ORCs) run by the Dhulikhel Hospital. However, the reasons behind this remain unclear. We aimed to examine the determinants of Nepalese rural dwellers' choice of first-contact health facility. # Methods This was a cross-sectional survey among 1,098 adult rural dwellers in Nepal. The study sample was first divided into PHC and ORC groups, and intergroup differences were tested using Pearson chi-square test and independent sample t-test. Then, binary logistic regression was performed to analyse first-contact health facility decision-making. # Results Sex, education level, importance of health care satisfaction, importance of free health care, diagnosis of hypertension, diagnosis of diabetes, insurance coverage, savings, community-level cooperation, and distance to the health facility were significant factors affecting the choice of the first-contact health facility. Most significantly, people who were unconcerned about receiving free health care were 19.417 times more likely to use ORCs. Additionally, it was observed that rural dwellers perceived ORCs as providing higher quality health care. # Conclusions The government must promote cooperation between PHCs and ORCs, as it is essential to understand consumer demand, supply-side issues, and institutional aspects of health care in rural areas to achieve universal access to health care.